Pentingnya Pendidikan Pola Hidup Sehat Di Era New Normal - Merri Silvia Basri; Fitria Nahdah Syariqoh; Dian Lamsihar Pakpahan; , Erika Zepania Br Garingging; Gustama Feraldi; Muhammad Faiz Nazya; Putra Trinanda.T; Putri Insani; Ratu Fiola; Wan Elisa Islamay; Witasha Afina Tusofia (Jurusan Ilmu Pendidikan - Universitas Lampung, 2022)
The Covid-19 pandemic has changed many things in a relatively short time. Educators and the community in responding to this condition require changes in clean and healthy living behavior in the new normal era. In the implementation of the New Normal phase, socialization is needed to the community, especially in the school environment with the aim of breaking the chain of spreading the Covid-19 virus, because the new normal does not mean that the environmental conditions are free from the Covid-19 virus, so you must remain vigilant. The service was carried out to the community and the school environment in Laksamana Village, Dumai City District, Riau Province. The method used is through socialization to the community and the school environment. This service activity is one of the work programs of the Balek Kampung Village Community Service Program, Laksamana 2022 as a form of knowledge transfer on ways to implement behavior change as an effort to prevent Covid-19. The results obtained in this service are that the community has the knowledge and ability to apply and motivate and adapt to family members, the community as pioneers in making changes to clean and healthy living behavior in the new normal era.